2020
DOI: 10.3233/jad-200516
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Anxiety and Incident Agitation in Alzheimer’s Disease

Abstract: Background: Agitation in Alzheimer’s disease (AD) has been hypothesized to be an expression of anxiety, but whether anxiety early in the course of dementia could be a risk factor for developing later agitation is unknown. Objective: We used the Alzheimer’s Disease Neuroimaging Initiative (ADNI) database to examine the longitudinal relationship between anxiety and incident agitation in individuals with a diagnosis of AD at baseline or during follow-up. Methods: Longitudinal neuropsychiatric symptom data from AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Anxiety tends to be more common in the early stages of the "dementia journey", while agitation is more common in later stages (35). Although the anxiety does not appear to be causally related to later agitation as has often been proposed (32), there is a clear association between the two constructs across stages of disease (36).…”
Section: Neuropsychiatric Symptoms: Prevalence Caregiver Challenge An...mentioning
confidence: 89%
“…Anxiety tends to be more common in the early stages of the "dementia journey", while agitation is more common in later stages (35). Although the anxiety does not appear to be causally related to later agitation as has often been proposed (32), there is a clear association between the two constructs across stages of disease (36).…”
Section: Neuropsychiatric Symptoms: Prevalence Caregiver Challenge An...mentioning
confidence: 89%
“…The results confirm the theory that both entities, agitation and anxiety, are distinct entities, and that furthermore, anxiety was not related to the future development of an agitation episode in Alzheimer patients at the beginning of the research, although a relationship between the two was found later. [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“… 37 , 50 Thus, our results further suggested more vascular network is to be mature and engaged in blood circulation after 8‐weeks EAST36 treatment. Considering that olfactory dysfunction and neuropsychiatric symptoms mutually interact with AD progression and precede the vast neurodegeneration in the brain, 27 , 51 , 52 , 53 treatment of olfactory dysfunction and neuropsychiatric symptoms is not only the issue of life quality improvement for the patient but also the intervention of AD progression. Excitedly, our data suggested that EAST36 treatment worked in this position by relieving early neurological symptoms and Aβ accumulation in cerebral vessels in AD mice, greatly downregulating the risks of progressive cognitive decline in AD.…”
Section: Discussionmentioning
confidence: 99%